Spatial richness patterns of soft-bottom fish in the Colombian Caribbean continental shelf and slope (2018)
This study presents a spatial analysis of species richness of soft-bottom bony and cartilaginous fish species in the Colombian Caribbean. The dataset consisted of 625 species distributed among 15651 georeferenced occurrences. The global richness completeness analysis suggests that the list is close to completion but that probably more species await being registered at greater depths. In spatial terms, our knowledge of fish richness remains incomplete as none of the spatial units, in which the general area was divided reached 100 % completeness and few reached 70 % or higher completeness probably due to the incidence of numerous rare species. The Guajira, Palomino, Tayrona and Golfo de Salamanca zones, displayed the highest observed and predicted richness. The Galerazamba, Arco (coralline archipelago) and Arboletes zones were predicted to have high species richness. In view of the results, marine protected areas need to be expanded to include soft-bottom habitats. Future research efforts should focus on the high species richness areas observed and predicted and surveys should include more extensively depth locations.